SELF DISCLOSURE MAHASISWA GEN Z DI MEDIA SOSIAL TIKTOK (STUDI PADA MAHASISWA UNIVERSITAS TEKNOLOGI SUMBAWA) - Utama, Nanda Fastika; Hidayat, Ofi (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
The phenomenon of TikTok usage among Generation Z is increasingly widespread, especially as a medium for self-expression or self-disclosure. TikTok has evolved beyond just entertainment; it now serves as a space for self-exploration, self-image construction, and social relationship building. Students at the University of Technology Sumbawa, as part of Generation Z, tend to share various aspects of their lives—ranging from daily activities and personal experiences to emotional expressions—through videos, captions, and music on TikTok. This study aims to explore the forms of self-disclosure practiced by students through TikTok. A descriptive qualitative approach is used, with data collection techniques including interviews, observation, and documentation. The Johari Window theory is applied in analyzing the data, dividing self-disclosure into four main areas: open, hidden, blind, and unknown. The results show that students' self-disclosure varies from openness and concealment of personal information to hidden potential. TikTok serves as a powerful space for self-expression, yet it is still shaped by cultural, privacy, and social norms.